2016
DOI: 10.3389/fpubh.2016.00142
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress among Ebola Survivors Discharged from an Ebola Treatment Unit in Monrovia, Liberia – A Qualitative Study

Abstract: IntroductionA consequence of the West Africa Ebola outbreak 2014–2015 was the unprecedented number of Ebola survivors discharged from the Ebola Treatment Units (ETUs). Liberia alone counted over 5,000 survivors. We undertook a qualitative study in Monrovia to better understand the mental distress experienced by survivors during hospitalization and reintegration into their community.MethodsPurposively selected Ebola survivors from ELWA3, the largest ETU in Liberia, were invited to join focus group discussions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
146
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(160 citation statements)
references
References 12 publications
5
146
0
2
Order By: Relevance
“…The Ebola treatment centers did not provide privacy, so those afflicted with EVD directly witnessed other patients (sometimes their own loved ones and children) in close proximity who were displaying the full spectrum of EVD symptoms, and sometimes “bleeding out” and dying, with the corpse remaining in view for hours [29••]. …”
Section: Overview Of Fear and Fear-related Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ebola treatment centers did not provide privacy, so those afflicted with EVD directly witnessed other patients (sometimes their own loved ones and children) in close proximity who were displaying the full spectrum of EVD symptoms, and sometimes “bleeding out” and dying, with the corpse remaining in view for hours [29••]. …”
Section: Overview Of Fear and Fear-related Behaviorsmentioning
confidence: 99%
“…The most identifiable individuals who are likely to experience serious and enduring psychological consequences are the 17,000 survivors who have recovered from EVD [5•]. A qualitative study of Ebola survivors who have received care in an ETU determined that psychological distress was widespread and related to direct exposures to suffering, death, and corpses left visible and unattended on the units while they were in treatment [29••]. …”
Section: Fear-related Behaviors In the 2013–2106 Evd Outbreakmentioning
confidence: 99%
“…Survivor programs have varied widely within and across the three most affected countries. According to interviews with survivors discharged from Liberia’s largest Ebola treatment unit, for example, many survivors lost jobs and housing, were separated from breadwinning family members, and were excluded from markets in which they could buy and sell products (Rabelo et al, 2016). Similar economic concerns have been documented in Guinea: a study of 121 Ebola survivors in urban parts of that country found most in poorer socioeconomic conditions, work situations, and workplace relationships following their acute illness than before it (Delamou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Liberia, for example, the Firestone Natural Rubber Company established a reintegration program in which the company’s medical personnel held meetings with survivors’ communities to allay concerns regarding the risks of Ebola transmission, organized community-wide celebrations to welcome survivors home, and visited survivors weekly for three months following discharge (Arwady et al, 2014). Counseling and other forms of psychosocial support have also been proposed as interventions to help survivors better cope with feelings of marginalization, isolation, guilt, distress, and shame (Mohammed et al, 2015; Rabelo et al, 2016), as have media engagement and public messaging to more broadly convey survivors’ stories and build acceptance (Karafillakis et al, 2016). Throughout West Africa, Ebola survivors and their supporters have created survivor networks, such as the Sierra Leone Association of Ebola Survivors (SLAES), to promote group healing and peer support, while advocating against stigma and drawing government and public attention to the unmet needs of thousands of survivors (Acland, 2016; SLAES, 2017; World Health Organization, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be challenging for survivors to access health care services. Survivors may face stigma within their community and in certain instances have lost their jobs and become isolated from the community [14]. …”
mentioning
confidence: 99%